Explosive Emergence of Colistin-Resistant and Carbapenem-Resistant Enterobacteriaceae (CRE) Among Community Food-Handlers in Kuwait. (4th October 2017) - **Al-Sweih, Noura; Moghnai, Ola; Rotimi, Vincent
Abstract: Background: Colistin is an antimicrobial agent used as last resorts for the treatment of carbapenem-resistant Enterobacteriaceae (CRE) and multidrug-resistant Gram-negative bacterial infections. Enterobacteriaceae cause urinary tract infections and other potentially life-threatening sepsis. The extent of colistin resistance and CRE among healthy individual food-handlers in the community is currently unknown. The aim of this study was to determine the prevalence of CRE and colistin-resistant isolates in faecal samples of healthy individuals with high occupational exposure to food in Kuwait. Methods: We included 400 food processing employees throughout Kuwait during their routine screening for Salmonella spp. Informed consent was obtained from each participant and the study was approved by local ethical committee. The rectal swab was collected and cultured using routine methodology for isolation. The identification was performed by Vitek-2 while the susceptibility was determined by measuring the MIC of antibiotics using the E-test. Results: A total of 679 non-duplicate isolates were included in the study. Out of these, 423, 125, and 53 were Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae, respectively. Seventy-seven (11.3%) individuals were positive for faecal carriage of colistin-resistant isolates (MIC, >2 mg/L). These isolates included E. coli ( n = 43), K. pneumoniae ( n = 14), E. cloacae ( n = 6), P. mirabilis ( n = 5), and 9 other species. The faecal carriage rate of CRE was 5.3%. 36). Isolates included[AU: Please clarify the significance of '36)' in '… 36. Isolates included . . .' in Abstract 'Explosive Emergence of Colistin-Resistant and . . .'] E. coli ( n = 16), K. pneumoniae ( n = 8). E. cloacae ( n = 3), Citrobacter spp. ( n = 2) and 7 other species. CRE was detected among 16.8% of colistin-resistant isolates; however, colistin resistance was detected in 15 (41.6%) of the CRE isolates. Conclusion: This study highlighted an unexpected and alarming high prevalence of colistin-resistant Enterobacteriaceae among healthy individuals working in various community eateries. Comparatively relatively lower prevalence of CRE was encountered. These findings call for introduction of preventive measures by Public Health Authority to prevent dissemination among the general population at large. Further genetic study is needed to evaluate the determinants of colistin resistance among the Enterobacteriaceae in our community. Disclosures: All authors: No reported disclosures.